Quejas y expectativas de estudiantes de licenciatura en lenguas extranjeras frente a las clases de inglés: estudio de caso desde el análisis crítico del discurso - Quiroz Posada, Ruth Elena; Díaz Monsalve, Ana Elsy (Colombian Applied Linguistics Journal, 2019)
A classroom-based case study was conducted as part of this research project to understand situations experienced by a group of students during their English classes. The students’ complaints and expectations in each context were identified. An overall workshop (Egg, 1999) was introduced in order to recognise such situations. The information collected through students’ complaints and expectations was processed on the basis of critical discourse analysis (Van Dijk, 2003), in addition to its interpretations from the perspectives of pedagogy and the theory of recognition (Honneth, 1997), thus, allowing to reveal students’ expectations of English classes beyond their complaints. These characteristics are related to educational categories and teachers’ qualities as regards professionalism, warmth and interaction. The lack of these expected characteristics and qualities makes meaningful English learning difficult because students are unable to experience fair conditions that are essential for their educational process in order to become comprehensive citizens, recognised in terms of love, law and solidarity.